2020
DOI: 10.1038/s41467-020-19225-7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic brain tumor delivery of synthetic protein nanoparticles for glioblastoma therapy

Abstract: Glioblastoma (GBM), the most aggressive form of brain cancer, has witnessed very little clinical progress over the last decades, in part, due to the absence of effective drug delivery strategies. Intravenous injection is the least invasive drug delivery route to the brain, but has been severely limited by the blood-brain barrier (BBB). Inspired by the capacity of natural proteins and viral particulates to cross the BBB, we engineered a synthetic protein nanoparticle (SPNP) based on polymerized human serum albu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
138
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 68 publications
0
138
0
Order By: Relevance
“…iRGD ligand exhibits more effective penetration ability and higher accumulation in tumors compared to the most of cyclic RGD ligands [ 40 ]. The most recent study demonstrates the crossing of blood-brain-barrier and systemic siRNA delivery to glioblastoma by means of iRGD-modified protein nanoparticles based on polymerized human serum albumin [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…iRGD ligand exhibits more effective penetration ability and higher accumulation in tumors compared to the most of cyclic RGD ligands [ 40 ]. The most recent study demonstrates the crossing of blood-brain-barrier and systemic siRNA delivery to glioblastoma by means of iRGD-modified protein nanoparticles based on polymerized human serum albumin [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that local treatment of glioma with sHDL (synthetic High-density lipoprotein) mimicking nanodiscs containing ApoAI mimetic peptide, phospholipids, immunogenic cell death inducing chemotherapeutics (ICD) docetaxel and adjuvant CpG oligodeoxynucleotide, effectively elicit anti-glioma T-cell activity and induce immunological memory response against tumor relapse (Kadiyala et al, 2019 ). We also engineered an albumin based NPs equipped with cell-penetrating iRGD peptide, containing siRNA against Signal Transducer and Activation of Transcription 3 factor (STAT3 i ) and demonstrated that when administered in combination with ionizing radiation, these NPs activate anti-GBM immunologic memory which results in tumor regression and long term survival of GBM bearing mice (Gregory et al, 2020 ). Other peptide modifications on nano-platforms have been explored to minimize off-target accumulation and facilitate active tumor targeting or mediate BBB transport.…”
Section: Gene Therapy and Virotherapy In Gliomamentioning
confidence: 99%
“… 8 Recently we developed and systemically administered 200 nm albumin-based-NP formulation to treat GBM bearing mice. 9 Our electro-hydrodynamic system is a new NP synthesis technology that can produce albumin-based NPs with distinct compartments. 8 In this system the rapid solvent evaporation induces nanoprecipitation resulting in particles with distinct compartments.…”
Section: Commentarymentioning
confidence: 99%